Cross-Border Data Flows and State Sovereignty: Balancing Globalization and National Security in the Digital Age - Karina, Ica; Korbaffo, Yosef Serano; Nurak, Ronaldus; Bria, Fridus; Taekab, Yosef Kristoforus; Sudirman, Irsyad (Jurnal Smart Hukum (JSH), 2025)
The rise of cross-border data flows has transformed global connectivity and economic integration, but it also challenges traditional notions of state sovereignty and national security. This article employs a qualitative research approach to analyze the legal, political, and technological dimensions of cross-border data governance. Focusing on the tension between global digital integration and the imperative to safeguard national interests, the study explores regulatory trends, state responses, and the evolving landscape of digital sovereignty. The findings highlight the need for balanced approaches that protect national security without stifling innovation and international cooperation.